Evaluation of the diagnostic performance of platelet-derived indices for the differential diagnosis of thrombocytopenia in pediatrics (2014)
Background. Platelet-derived indices have a well-established correlation with the differential diagnosis of thrombocytopenia in adult-based research. These indices include mean platelet volume, platelet distribution width, and platelet-large cell ratio.Objective. To determine the values of platelet-derived indices in a pediatric population with diagnoses of thrombocytopenia and their etiologic correlation.Materials and methods. Analytic observational diagnostic-test study. The population for this analytical study was pediatric patients between 6 months and 18 years of age who had thrombocytopenia (100x109/L). The study period was 18 months long.Results. Of 54 subjects, 18 (33.3%) were diagnosed with idiopathic thrombocytopenic purpura, and 36 (66.7%) were diagnosed with acute leukemia. Mean age was 7.4 years and 6.8 years for immune thrombocytopenic purpura and acute leukemia, respectively. Mean platelet distribution width values for immune thrombocytopenic purpura and acute leukemia were 15.08 fL and 10.73, respectively. Mean MPV for immune thrombocytopenic purpura and acute leukemia was 11.7 fL and 9.8 fL, respectively. Mean platelet-large cell ratio was 38.26% and 24.97% for idiopathic thrombocytopenic purpura and acute leukemia, respectively. Differences in these three distinct platelet indices between idiopathic thrombocytopenic purpura and acute leukemia were statistically significant (p=0.00). The area under the ROC curve for platelet-derived indices showed that they were adequate for defining the causes of thrombocytopenia. MPV and platelet-large cell ratio had an area under the curve of 0.89 and 0.88, respectively, while platelet size deviation width had an area under the curve of 0.903.Conclusions. Platelet-derived indices could be useful in the initial approach for the differential diagnosis of pediatric patients with thrombocytopenia.